Edible Films and Coatings as Carriers of Living Microorganisms: A New Strategy Towards Biopreservation and Healthier Foods. Issue 3 (30th March 2018) - Guimarães, Ana; Abrunhosa, Luís; Pastrana, Lorenzo M.; Cerqueira, Miguel A.
Abstract: Edible films and coatings have been extensively studied in recent years due to their unique properties and advantages over more traditional conservation techniques. Edible films and coatings improve shelf life and food quality, by providing a protective barrier against physical and mechanical damage, and by creating a controlled atmosphere and acting as a semipermeable barrier for gases, vapor, and water. Edible films and coatings are produced using naturally derived materials, such as polysaccharides, proteins, and lipids, or a mixture of these materials. These films and coatings also offer the possibility of incorporating different functional ingredients such as nutraceuticals, antioxidants, antimicrobials, flavoring, and coloring agents. Films and coatings are also able to incorporate living microorganisms. In the last decade, several works reported the incorporation of bacteria to confer probiotic or antimicrobial properties to these films and coatings. The incorporation of probiotic bacteria in films and coatings allows them to reach the consumers' gut in adequate amounts to confer health benefits to the host, thus creating an added value to the food product. Also, other microorganisms, either bacteria or yeast, can be incorporated into edible films in a biocontrol approach to extend the shelf life of food products. The incorporation of yeasts in films and coatings has been suggested primarily for the control of the postharvest disease. This work provides a comprehensive review of the use of edible films and coatings for the incorporation of living microorganisms, aiming at the biopreservation and probiotic ability of food products.